The Use of Medicinal Plant-Derived Metallic Nanoparticles in Theranostics - Jabulile Happiness Xulu; Tanaka Ndongwe; Kenneth M. Ezealisiji; Vuyelwa J. Tembu; Nontobeko P. Mncwangi; Bwalya A. Witika; Xavier Siwe-Noundou (MDPI AG, 2022)
In the quest to effectively diagnose and treat the diseases that afflict mankind, the development of a tool capable of simultaneous detection and treatment would provide a significant cornerstone for the survival and control of these diseases. Theranostics denotes a portmanteau of therapeutics and diagnostics which simultaneously detect and treat ailments. Research advances have initiated the advent of theranostics in modern medicine. Overall, theranostics are drug delivery systems with molecular or targeted imaging agents integrated into their structure. The application of theranostics is rising exponentially due to the urgent need for treatments that can be utilized for diagnostic imaging as an aid in precision and personalised medicine. Subsequently, the emergence of nanobiotechnology and the green synthesis of metallic nanoparticles (MNPs) has provided one such avenue for nanoscale development and research. Of interest is the drastic rise in the use of medicinal plants in the synthesis of MNPs which have been reported to be potentially effective in the diagnosis and treatment of diseases. At present, medicinal plant-derived MNPs have been cited to have broad pharmacological applications and have been studied for their potential use in the treatment and management of cancer, malaria, microbial and cardiovascular diseases. The subject of this article regards the role of medicinal plants in the synthesis of MNPs and the potential role of MNPs in the field of theranostics.